2015
DOI: 10.1016/j.juro.2015.06.081
|View full text |Cite
|
Sign up to set email alerts
|

PnPP-19, a Synthetic and Nontoxic Peptide Designed from a Phoneutria nigriventer Toxin, Potentiates Erectile Function via NO/cGMP

Abstract: PnPP-19 potentiates erection in vivo and ex vivo via the nitric oxide/cyclic guanosine monophosphate pathway. It does not affect sodium channels or rat hearts and shows no toxicity and low immunogenicity. These findings make it a promising candidate as a novel drug in the therapy of erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 27 publications
6
45
0
Order By: Relevance
“…Interestingly, the extra Asn-23 residue present in ocellatin-LB2 sequence seems to decrease its antimicrobial potential and the strength of the peptide-membrane interactions in comparison to ocellatin-LB1. In this sense, it seems to be worth in future investigations to promote site-directed substitutions at Asn-23 in ocellatin-F1 sequence in order to improve the biological activities of this peptide series [50]. Naturally, structural and topological information obtained from other biophysical approaches, such as solution and solid-state NMR spectroscopies [46, 51], can be used to gain information about the peptide-membrane interaction process and may give important insights about the amino acid substitutions at position 23, which can easily be performed by solid-phase peptide synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the extra Asn-23 residue present in ocellatin-LB2 sequence seems to decrease its antimicrobial potential and the strength of the peptide-membrane interactions in comparison to ocellatin-LB1. In this sense, it seems to be worth in future investigations to promote site-directed substitutions at Asn-23 in ocellatin-F1 sequence in order to improve the biological activities of this peptide series [50]. Naturally, structural and topological information obtained from other biophysical approaches, such as solution and solid-state NMR spectroscopies [46, 51], can be used to gain information about the peptide-membrane interaction process and may give important insights about the amino acid substitutions at position 23, which can easily be performed by solid-phase peptide synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, PnTx3-3 (ω ctenitoxin Pn2a) and Phα1β induce an antinociceptive effect in neuropathic pain models [4, 5]. More recently, we have shown that the synthetic peptide, PnPP-19, firstly characterized as a potentiator of erectile function, also produces antinociception in rats when peripherally injected [1, 17]. We also showed that this peripheral effect involves inhibition of neutral endopeptidase (NEP) (EC 3.4.24.11), and activation of CB 1 , μ- and δ-opioid receptors [17].…”
Section: Discussionmentioning
confidence: 99%
“…PnPP-19 is a synthetic peptide that contains 19 amino acid residues [1]. It represents a part of the primary structure of the native toxin PnTx2-6, also known as δ-ctenitoxin-Pn2a [2], which was isolated from the venom of the spider Phoneutria nigriventer [3].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these compounds seemed to preferentially aim at testicles and penis [76] but at a site different from that targeted by sildenafil (Viagra ® ) [81]. Notably, intraperitoneal injection of PnTx2-6 induced priapism in laboratory mice at doses that avoided most of the systemic toxic symptoms [84], and attempts to synthesize analogues with retained erectogenic effect but minimal side effects gave promising results [78,85]. Still, further studies are necessary to evaluate the safety of these compounds as drugs for human use.…”
Section: Cheliceratamentioning
confidence: 99%